I. I. Tchaikovsky in Management of Black Sea - Baltic Shipping Line in 1894—1896 - M. N. Baryshnikov (Научный диалог)
The contribution of I. I. Tchaikovsky, head of the St. Petersburg agency of the Russian Society of Shipping and Trade (RSST= ROPiT), to the development of trade relations between St. Petersburg and the Russian Black Sea ports in 1894—1896 is analyzed. The result is comparative indicators of cargo transportation between the Russian capital and major port cities, the quantity, range and directions of commodity flows, their belonging to specific entrepreneurs and firms are revealed. Using a variety of archival data, it is shown that under the leadership of Tchaikovsky, the Black Sea-Baltic shipping line had a positive impact on the development of interregional trade relations. The agency's activities are seen as an example of business operations that have changed the dynamics of large cabotage, increasing the importance of sea freight by combining regularity with regional demand for industrial and agricultural products. The role of Tchaikovsky as a leader is interpreted in the context of his search and implementation of a balance between the preferences of individuals, firms and government agencies interested in the activities of the Black Sea-Baltic line, on the one hand, and the corporate interests of RSST (ROPiT) in their strategic (ensuring the growth of domestic and cross-border cargo transportation) content - on the other side.